2017
DOI: 10.15376/biores.12.3.4707-4721
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Kinetic Behaviors of Fallen Leaves and Waste Tires Using Thermogravimetric Analysis

Abstract: Thermal decomposition characteristics and kinetic parameters of fallen leaves (FLs), waste tires (WTs), and their blends (1:1 weight ratio) were investigated. Pyrolysis experiments were conducted with four different heating rates of 5 °C/min, 10 °C/min, 20 °C/min, and 40 °C/min from 35 °C to 800 °C in a nitrogen atmosphere using a thermogravimetric analysis (TGA). The thermogravimetry/derivative thermogravimetry (TG/DTG) curves indicated that the three samples were mainly degraded in a wide temperature range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Even so, authors' opinion is that it is acceptable because same deviations are presented in other researches [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Results Of the Kinetic Analysismentioning
confidence: 90%
“…Even so, authors' opinion is that it is acceptable because same deviations are presented in other researches [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Results Of the Kinetic Analysismentioning
confidence: 90%
“…The dependence of the "thermal residual mass" on temperature for PEO powder (left) PEO nanofibers spun from water solution (middle) and PEO nanofibers obtained from chloroform solutions subjected to different heating rates. In the left and middle graphs, the symbols identify experimental data and the dotted lines represent best fits obtained by using Equation (23). In the right panel the broader lines represent experimental data, and the narrow darker lines represent the best fits obtained by using Equation ( 23 The experimental data were represented by various symbols for PEO powder (left graph) and PEO mats obtained from water solutions (middle graph), while the best fit was represented by dotted lines.…”
Section: Resultsmentioning
confidence: 99%
“…A similar expression was derived by Flynn-Wall-Ozawa (FWO). 15 More detailed calculations suggested that the actual slope within the Flynn-Wall-Ozawa approximation is 1.052 E A / R 19,22 or 0.4567 E A /R 20,[23][24][25] and not precisely E A /R (where R is the ideal gas constant). While some authors claimed that this model does not consider the details on the thermal degradation, it is essential to note that F(γ) should not depend explicitly on time or temperature.…”
Section: Connections To Existing Theories and Modelsmentioning
confidence: 99%
“…Later, those Ea were inserted into the Coats-Redfern adjustment model to calculate the pre-exponential factors based on a first-order reaction speed. It is important to note that the amount of hydrogen reported in the elemental analysis of the leaves + tires mixture was 6.25% [36]. A different study of discarded tires determined an average Ea of 162.8 ± 23.2 kJ mol −1 , using the KAS and FWO methods and the Master Plot approach in a mass conversion range (a) of 0.20-0.80.…”
Section: Kinetics Of Lignocellulosic Materialsmentioning
confidence: 99%